Spontaneous Imbibition Experiment and Main Influence Factors in Ultra-Low-Permeability Reservoirs. (3rd April 2023) - Shi, Lihua; Li, Hong; Shi, Tiaotiao; Hou, Binchi; Xue, Ying; Shen, Zhenzhen; Zeng, Jun
Abstract : The imbibition has an important influence on the water injection development of ultra-low-permeability reservoirs. In this paper, the nuclear magnetic resonance (NMR) high-temperature and high-pressure displacement system was used to simulate the formation temperature and pressure and the spontaneous imbibition of single porosity medium and dual porosity medium (containing fractures), and imbibition displacement experiments at different injection rates were carried out. The NMR T2 spectrum curves of simulated oil signals in the pores, throats, and fractures were obtained. The characteristics of oil content change and oil displacement efficiency in dual porosity medium under different experimental conditions were quantitatively evaluated, and the contribution of spontaneous imbibition to oil displacement efficiency was clarified. The experimental results show that the oil displacement efficiency of single porosity medium is lower than that of dual porosity medium. The smaller the pore is, the greater the displacement speed is, and the greater the contribution rate of imbibition is. The porosity, permeability, and maximum pore throat radius are positively correlated with the oil displacement efficiency of spontaneous imbibition but are poorly correlated with the oil displacement efficiency of under the dual action of spontaneous imbibition and displacement. The poor correlation also includes the median pressure, maximum mercury saturation, median radius, and displacement rate. Fractures play a positive role in improving oil displacement efficiency.